2015
DOI: 10.1111/obr.12317
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high‐intensity interval training on glucose regulation and insulin resistance: a meta‐analysis

Abstract: Summary The aim of this meta‐analysis was to quantify the effects of high‐intensity interval training (HIIT) on markers of glucose regulation and insulin resistance compared with control conditions (CON) or continuous training (CT). Databases were searched for HIIT interventions based upon the inclusion criteria: training ≥2 weeks, adult participants and outcome measurements that included insulin resistance, fasting glucose, HbA1c or fasting insulin. Dual interventions and participants with type 1 diabetes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
314
5
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(379 citation statements)
references
References 118 publications
(127 reference statements)
31
314
5
13
Order By: Relevance
“…Moreover, patients should avoid dehydration when exercising to avoid intestinal hypoperfusion. Use of high-intensity interval training in patients with IBD may reveal metabolic benefits similar to those seen in obesity [67] and diabetes [68] but this has not been comprehensively investigated. Also, the protective effect of regular physical activity on bone mineral density in IBD sufferers is largely unknown with a recent meta-analysis identifying only a single suitable exercise-intervention study [69].…”
Section: Metabolic and Immunological Effects Of Exercisementioning
confidence: 99%
“…Moreover, patients should avoid dehydration when exercising to avoid intestinal hypoperfusion. Use of high-intensity interval training in patients with IBD may reveal metabolic benefits similar to those seen in obesity [67] and diabetes [68] but this has not been comprehensively investigated. Also, the protective effect of regular physical activity on bone mineral density in IBD sufferers is largely unknown with a recent meta-analysis identifying only a single suitable exercise-intervention study [69].…”
Section: Metabolic and Immunological Effects Of Exercisementioning
confidence: 99%
“…Aerobic activity bouts should ideally last at least 10 min, with the goal of ;30 min/day or more, most days of the week for adults with type 2 diabetes. Daily exercise, or at least not allowing more than 2 days to elapse between exercise sessions, is recommended to decrease insulin resistance, regardless of diabetes type (129,130). Over time, activities should progress in intensity, frequency, and/or duration to at least 150 min/week of moderate-intensity exercise.…”
Section: Frequency and Type Of Physical Activitymentioning
confidence: 99%
“…High-intensity interval training (HIT) has been proposed to represent a promising, time-efficient alternative/adjunct to aerobic exercise (Earnest, 2008). Meta-analyses have demonstrated that, compared to aerobic exercise, HIT is more effective at improving insulin resistance (Jelleyman et al, 2015) and V O2max (Milanovic et al, 2015) in healthy sedentary individuals. In T2D patients, HIT has been shown to be associated with improvements in insulin sensitivity (Karstoft et al, 2014), glycaemic control (Little et al, 2011), and endothelial function (Madsen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%